Infant mortality due to preventable causes - Katiane da Silva Mendonça; Ana Carolyna da Silva Rocha; Karen Samylle Calado de Melo Marques; Lais Valeria da Silva Bispo; Roberta Zaninelli do Nascimento; Christefany Régia Braz Costa (Revista Uningá, 2022)
Infant mortality refers to deaths of children under one year of age, subdivided into neonatal mortality (early and late neonatal) and post-neonatal mortality, being considered an indicator for assessing the population's health situation. The study aimed at describing the infant mortality rates due to preventable causes, in children under one year of age and in the state of Alagoas, during 2017. A descriptive and cross-sectional ecological study was carried out, with a quantitative approach on mortality rates in the age group of children under one year old, based on secondary data available in the Mortality Information System, by the Informatics Department of the Unified Health System (Departamento de Informática do Sistema Único de Saúde, [DATASUS]). This study was carried out from November to December 2019. During this period, in the state of Alagoas, 793 deaths due to preventable causes among children under five years of age were recorded in the Informatics Department of the Unified Health System. 83.98% (n=666) of these deaths corresponded to children under one year of age, with death cases in the early neonatal period being the most prevalent, followed by deaths in the post-neonatal and late neonatal periods. Among the cities in Alagoas, Maceió ranks first and Arapiraca is in second place in relation to the infant mortality rate.